Impact of UCP1 and β3AR gene polymorphisms on age-related changes in brown adipose tissue and adiposity in humans - Yoneshiro, T; Ogawa, T; Okamoto, N; Matsushita, M; Aita, S; Kameya, T; Kawai, Y; Iwanaga, T; Saito, M (International Journal of Obesity, 2013)
Background: Brown adipose tissue (BAT) is involved in the regulation of whole-body energy expenditure and adiposity. The activity and prevalence of BAT decrease with age in humans. Objective: To examine the effects of single nucleotide polymorphisms of the genes for uncoupling protein 1 ( UCP1 ) and β3-adrenergic receptor ( β3AR ), key molecules of BAT thermogenesis, on age-related decline of BAT activity and accumulation of body fat in humans. Methods: One hundred ninety-nine healthy volunteers (20–72 years old (y.o.)) underwent fluorodeoxyglucose-positron emission tomography (FDG-PET) and computed tomography (CT) after 2-h cold exposure to assess BAT activity. The visceral and subcutaneous fat areas at the abdominal level were estimated from the CT images. They were genotyped for −3826 A/G polymorphism of the UCP1 gene and 64 Trp/Arg mutation of the β3AR gene. Results: BAT was detected in 88 subjects out of 199 (44%), more in younger (⩽30 y.o., 55%) than older subjects (>40 y.o., 15%). BAT prevalence of older subjects tended to be lower in the UCP1 G/G group than the A allele group (A/A and A/G), and also in the β3AR Arg allele group (Trp/Arg and Arg/Arg) than the Trp/Trp group. When compared subjects who had two or more base substitutions on the two genes (the 2–4 allele group) with those who had less than two base substitutions (the 0–1 allele group), BAT prevalence was comparable in younger subjects (62% vs 50%) but lower in older subjects (0% vs 24%, P <0.05). Visceral fat area of the 2–4 allele group was higher than that of the 0–1 allele group ( P <0.05) in older subjects, but not in younger subjects. Conclusion: UCP1 −3826 A/G and β3AR 64 Trp/Arg substitutions accelerate age-related decrease in BAT activity, and thereby may associate with visceral fat accumulation with age.